Analysis of Direct and Indirect Selection and Indices in Bread Wheat (Triticum aestivum L.) Segregating Progeny - Zine El Abidine Fellahi; Abderrahmane Hannachi; Hamenna Bouzerzour (International Journal of Agronomy)
Three selection methods including direct and indirect selection along with selection index based on the phenotypic values of eleven traits of agronomic interest were assessed for their application in F4 bread wheat progenies. Significant genetic variation existed among parents and crosses for the traits measured. The following were the most efficient indices for simultaneous selection of superior lines for yield and its components: base index of Williams, followed by the sum of ranks index of Smith and Hazel. The selection-based index provided the highest grain yield gains as compared to the other selection criteria, except for flag leaf area, indicating that the direct and indirect monotrait selection were not appropriate in the situation analyzed in this work. PCA identified Ain Abid × Mahon-Demias, Ain Abid × Rmada, and Ain Abid × El-Wifak as the most promising populations. At 5% selection intensity, the top 30 lines selected were distinguished, in comparison with the standard check Hidhab, by significant improvements in yield and yield components.